2001
DOI: 10.1128/aem.67.7.3077-3085.2001
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Diversity of the Brine-Seawater Interface of the Kebrit Deep, Red Sea, Studied via 16S rRNA Gene Sequences and Cultivation Methods

Abstract: The brine-seawater interface of the Kebrit Deep, northern Red Sea, was investigated for the presence of microorganisms using phylogenetic analysis combined with cultivation methods. Under strictly anaerobic culture conditions, novel halophiles were isolated. The new rod-shaped isolates belong to the halophilic genus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
99
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(102 citation statements)
references
References 67 publications
(62 reference statements)
3
99
0
Order By: Relevance
“…These contrasting conditions are likely to influence the composition, vertical distributions and level of abundances of the microbial communities strongly. However, only two primary studies of microbial diversity at the brine-seawater interface have been carried out at the Kebrit and Shaban Deeps in the Red Sea (Eder et al, 2001(Eder et al, , 2002 and microbial communities in water column of the Red Sea have yet to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…These contrasting conditions are likely to influence the composition, vertical distributions and level of abundances of the microbial communities strongly. However, only two primary studies of microbial diversity at the brine-seawater interface have been carried out at the Kebrit and Shaban Deeps in the Red Sea (Eder et al, 2001(Eder et al, , 2002 and microbial communities in water column of the Red Sea have yet to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…The deep brine pools of the Red Sea, located along tectonic rift systems on its seabed, are considered an unexplored and remote source with high potential for the discovery of novel extremophilic enzymes (Grötzinger et al 2014 ;Antunes et al 2011 ;Eder et al 2001 ). Temperatures in these brine pools vary from 23.3 °C (Kebrit) to 68.2 °C (Atlantis II) with salinities of 25 to 28 % (w/v) (Antunes et al 2011 ;Wang et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, DHABs in the Mediterranean and Red Sea have provided exciting new insights into novel microbial diversity and have extended our knowledge of environmental factors that define the limits of life (Eder et al, 1999(Eder et al, , 2001Hallsworth et al, 2007). Studies of Discovery, L'Atalante, Urania, Thetis and Bannock basins revealed that DHAB interfaces harbor abundant and diverse microbial communities that include numerous novel candidate divisions that are more productive than most pelagic marine systems (see, for example, Sass et al, 2001;Van Der Wielen et al, 2005;Yakimov et al, 2007;Edgcomb et al, 2009;Stock et al, 2012).…”
Section: Introductionmentioning
confidence: 99%